Capillary-bridge mediated assembly of aligned perovskite quantum dots for high-performance photodetectors. Issue 20 (29th April 2019) - Dai, Zhigao; Ou, Qingdong; Wang, Chujie; Si, Guangyuan; Shabbir, Babar; Zheng, Changxi; Wang, Ziyu; Zhang, Yupeng; Huang, Yamin; Dong, Yemin; Jasieniak, Jacek J.; Su, Bin; et al.
Abstract : A liquid bridge induced assembly strategy to align perovskite QDs in one direction for high-performance photodetectors. Abstract : Effective assembly of perovskite quantum dots is a huge challenge to develop high-performance optoelectronic devices with large scale integration functionality. Here, we demonstrate a facile way to fabricate one-dimensional arrays consisting of aligned perovskite quantum dots and their remarkable application as high-performance photodetectors. All inorganic perovskite CsPbX3 (X = Cl, Br, I) quantum dots, synthesized by a hot injection method, are precisely assembled into the one-dimensional arrays using a liquid bridge induced assembly strategy. Systematic studies have shown that photodetectors based on such one-dimensional CsPbI3 quantum dot arrays have excellent performance in terms of high responsivity and high detection sensitivity. It is suggested that the availability of more oxygen-rich hole trapping states on the surface of the quantum dots play an important role in the photocurrent generation. This work presents a significant step forward towards scalable self-assembly of perovskite quantum dots into one-dimensional arrays, indicating an enormous potential in manufacturing of high-performance integrated optoelectronic sensor circuitry.